FACTORS AFFECTING THE PERFORMANCE OF REGIONAL HOUSE OF REPRESENTATIVES (DPRD) MEMBERS IN REGIONAL FINANCIAL SUPERVISION WITH WORK COMMITMENTS AS MODERATING VARIABLES (Empirical Study In The Regional House of Representatives Office of South Labuhan Batu Re - Harahap, Ralianja (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to analyze work commitments able to moderate between the council’s knowledge of the budget, public/community participation, transparency and accountability on the performance of Regional House of Representatives(hereinafter will be referred as DPRD) members in regional financial supervision in South Labuhan Batu. The results are: 1) the council’s knowledge of the budget, transparency and accountability has a significant effect on on the performance of DPRD members in regional financial supervision 2) Community participation does not significantly affect the performance of DPRD members in regional financial supervision 3) work commitments are not able to moderate the knowledge of the council on the budget, community participation, transparency and accountability on the performance of DPRD members in financial supervision area in South Labuhan Batu.